Hydrogen sulfide attenuates diabetic neuropathic pain through NO/cGMP/PKG pathway and μ-opioid receptor. Issue 9 (May 2020) - Li, Hao; Liu, Shulin; Wang, Zheng; Zhang, Yonglai; Wang, Kaiguo
Diabetic neuropathic pain is a frequent complication of diabetic neuropathy. The specific manifestations of diabetic neuropathic pain include spontaneous pain and hyperalgesia, which seriously affect the quality of life of patients. Previous publications have shown that H2 S has both pro-nociceptive and anti-nociceptive effects. This present investigation aimed to examine the anti-nociceptive effect of H2 S on diabetic neuropathic pain. We established a diabetic neuropathic pain animal model with high-glucose, high-fat diet, and STZ, then treated rats with different concentrations of H2 S and inhibitors of NOS, sGC, PKG, and opioid receptors. The mechanical allodynia and thermal hyperalgesia of rats were measured to assess the anti-nociceptive effects of H2 S. The mRNA and protein expression of NOS and PKG1 were measured to explore their roles in the anti-nociceptive action of H2 S. The results revealed that inhalation of H2 S gas had anti-nociceptive effect in diabetic neuropathic pain model rats without affecting the blood glucose level and body mass. It increased the mRNA and protein level of nNOS, and the inhibitor of nNOS, 7-NI, abolished the anti-nociceptive effect of H2 S. Furthermore, inhibitors of sGC and PKG could also abolish the anti-nociceptive effect of H2 S. The expression of PKG1 was found to be increased by H2 S, which was reversed by the inhibitors of nNOS, sGC, and PKG. Finally, CTOP, a μ-opioid receptor antagonist, abolished the anti-nociceptive effect of H2 S, indicating that the μ-opioid receptor plays a role in the anti-nociceptive effect of H2 S. In conclusion, the findings of this investigation suggest that hydrogen sulfide may attenuate the diabetic neuropathic pain through NO/cGMP/PKG pathway and μ-opioid receptor. Impact statement: There are currently approximately 425 million diabetic patients worldwide, of which approximately 90% of patients with diabetes suffer from neuropathy. Diabetic neuropathic pain (DNP) is a common complication of diabetic neuropathy. Nearly half of the patients hospitalized with diabetes have pain symptoms or symptoms related to neurological injury, and the incidence increases with age and diabetic duration. Anti-DNP analgesics have either limited therapeutic effects or serious side effects or lack of clinical trials, which has limited their application. Physiopathological mechanisms and treatment of DNP remain a significant challenge. The present confirmed that inhalation of H2 S may attenuate the diabetic neuropathic pain through NO/cGMP/PKG pathway and μ-opioid receptor. It provides us the animal study foundation for the application of H2 S on the treatment of DNP and clarifies some target molecules in the pain modulation of DNP.